1985
DOI: 10.1152/jappl.1985.59.5.1503
|View full text |Cite
|
Sign up to set email alerts
|

Decompression outcome following saturation dives with multiple inert gases in rats

Abstract: This investigation examined the question of whether gas mixtures containing multiple inert gases provide a decompression advantage over mixtures containing a single inert gas. Unanesthetized male albino rats, Rattus norvegicus, were subjected to 2-h simulated dives at depths ranging from 145 to 220 fsw. At pressure, the rats breathed various He-N2-Ar-O2 mixtures (79.1% inert gas-20.9% O2); they were then decompressed rapidly (within 10 s) to surface pressures. The probability of decompression sickness (DCS), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 0 publications
5
39
1
Order By: Relevance
“…The dosage we tested was nearly double that of Popovic et aI., but we administered ASA for 3 d predive, versus 30 d predive in the Popovic et al study. Our dives saturated the rats with nitrogen (29), whereas the Popovic dives were of 30 min duration, which is subsaturated. We do not know how these differences in protocol may have contributed to the disparate results.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The dosage we tested was nearly double that of Popovic et aI., but we administered ASA for 3 d predive, versus 30 d predive in the Popovic et al study. Our dives saturated the rats with nitrogen (29), whereas the Popovic dives were of 30 min duration, which is subsaturated. We do not know how these differences in protocol may have contributed to the disparate results.…”
Section: Discussionmentioning
confidence: 85%
“…Dive protocols were derived from the work of Lillo et al, with pressure and duration selected for a high inci dence of DCS in untreated rats of this body mass (29). Rats were exposed in groups of 4 per dive, approxi mately 40 per experimental group, for a total of 633 ani mals for this study.…”
Section: Dive Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it does not achieve significance, there is a trend for increasing animal weight to increase the risk of DCS. Lillo et al (18) found a stronger weight dependence in rats, presumably because of a wider relative weight range. Neither age nor weight change during the dive (a surrogate for respiratory and urinary fluid losses) was significant here.…”
Section: Discussionmentioning
confidence: 94%
“…Years of experience with the maximum likelihood technique have shown that a large number of experiments are necessary to solve problems such as differences in gas potencies for inducing DCS (Lillo, 1988;Lillo and MacCallum, 1991), or asymmetrical exchange kinetics for compression and decompression (Thalmann et al, 1997;Lillo and Parker, 2000). Since large data sets are not always feasible, some studies have limited the physiological models by either restricting the complexity of the model or restricting the experiments to a small number of compression and decompression sequences (Lillo et al, 1985;Lillo, 1988). The present study likewise separated the experiments into those that featured changes in time spent at constant pressure, and those that featured changes in time spent during decompression.…”
Section: Discussionmentioning
confidence: 99%